La Consueta de la parròquia de Sant Pere de Viladecavalls (c. 1654) - Galobart i Soler, Josep (Miscel·lània litúrgica catalana, 2007)
The custom book of the parish of Sant Pere de Viladecavalls in the Calders borough, located in the Moianès county, composed in the second third of the 17th century, belongs to the so-called modern epoch. It is quite an interesting document for knowing liturgical and devotional practice, life and organization in a rural parish as well as the economy of its management. With the publication of this custom book, the author goes on providing both liturgy and Catalan church history scholars with 16th and 17th century customaries of the parishes of the Bages and Moianès counties.